1997
DOI: 10.1093/hmg/6.3.465
|View full text |Cite
|
Sign up to set email alerts
|

A novel human homologue of the Drosophila frizzled wnt receptor gene binds wingless protein and is in the Williams syndrome deletion at 7q11.23

Abstract: Williams syndrome (WS) is a developmental disorder with a characteristic personality and cognitive profile that is associated, in most cases, with a 2 Mb deletion of part of chromosome band 7q11.23. By applying CpG island cloning methods to cosmids from the deletion region, we have identified a new gene, called FZD3. Dosage blotting of DNA from 11 WS probands confirmed that it is located within the commonly deleted region. Sequence comparisons revealed that FZD3, encoding a 591 amino acid protein, is a novel m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
119
1
1

Year Published

1998
1998
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(124 citation statements)
references
References 31 publications
3
119
1
1
Order By: Relevance
“…12 Other genes since identified are shown in Table 1. [13][14][15][16][17][18][19][20][21][22] All these genes appear to be deleted in most WS patients. No phenotype has been clearly assigned to haploinsufficiency for any of them and some are deleted in patients ascertained through SVAS who do not have WS.…”
Section: Introductionmentioning
confidence: 99%
“…12 Other genes since identified are shown in Table 1. [13][14][15][16][17][18][19][20][21][22] All these genes appear to be deleted in most WS patients. No phenotype has been clearly assigned to haploinsufficiency for any of them and some are deleted in patients ascertained through SVAS who do not have WS.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, we characterize a recently identified Frizzled family member, Frizzled-9, in Wnt/␤-catenin signaling. Frizzled-9 is highly expressed in the brain, and its gene is one of several genes that are deleted in a developmental disorder, Williams syndrome (29,30). The gene deletion is thought to contribute to the neurological symptoms of Williams syndrome (29,30).…”
mentioning
confidence: 99%
“…Frizzled-9 is highly expressed in the brain, and its gene is one of several genes that are deleted in a developmental disorder, Williams syndrome (29,30). The gene deletion is thought to contribute to the neurological symptoms of Williams syndrome (29,30). We demonstrate that rat Frizzled-9 (Rfz9) functions in Wnt/␤-catenin signaling in mammalian cells and that Rfz9 can act as a receptor for Wnt-2.…”
mentioning
confidence: 99%
“…29 Frizzled 3 which is expressed in highest levels in adult brain 7 was previously shown to be located within the 2-Mb deletion region of chromosome band 7q11.23 that was associated with the developmental disorder, Williams syndrome (WS). 30 The deleted sequence within chromosome band, 7q11.23, encodes frizzled 3 that may contribute to the WS phenotype. 30 RHM indicated that frizzled 3 was most closely linked to a marker D7S2101E, at 7q11.21.…”
Section: Discussionmentioning
confidence: 99%
“…30 The deleted sequence within chromosome band, 7q11.23, encodes frizzled 3 that may contribute to the WS phenotype. 30 RHM indicated that frizzled 3 was most closely linked to a marker D7S2101E, at 7q11.21. This linked marker was located 40 cR from locus D7S672 that was more proximal to the telomeric end of chromosome 7q.…”
Section: Discussionmentioning
confidence: 99%